Synthesis Of Zinc Selenide Coated By Zinc Sulfide Nanoparticles Via Modified Polyol Method - Lee, See Yau (2011)

(untitled)
Zinc selenide (ZnSe) nanoparticles and zinc selenide@zinc sulphide (ZnSe@ZnS) core-shell structure were prepared using a surfactant-assisted process. ZnSe nanoparticles were prepared using zinc chloride and selenium powder as the precursor sources. The obtained ZnSe nanoparticles were then coated with ZnS to form the ZnSe@ZnS core-shell structure. Various parameters namely processing time, processing temperature, precursor ratio, concentration of surfactant, molecular weight of surfactant, and type of surfactant have been studied in order to produce finer particle with narrow particle size distribution of the ZnSe and ZnSe@ZnS coreshell nanoparticles.